Investigation on the content quality and clinical applicability of the Traditional Chinese Medicine nursing program (中医护理方案的内容质量和临床适用性的现状调查研究) - CHEN Hong (陈宏); TANG Ling (唐玲); LI Xuejing (李学靖) (中西医结合护理)
Objective To develop a self-made questionnaire on the content quality and clinical applicability of Traditional Chinese Medicine (TCM) nursing program. The content, quality and clinical applicability of TCM nursing plan in acute and convalescent stage of stroke were evaluated by clinical nurses through questionnaire. Methods The questionnaire was designed with reference to the questionnaire on the applicability of clinical diagnosis and treatment guidelines of TCM, and the content validity was evaluated by expert consultation. Totally 49 nurses from 9 hospitals were selected for questionnaire survey, and the questionnaire results were processed and analyzed by SPSS 20. 0 software. Results The content validity S-CVI/Ave score of the self-designed questionnaire was 0. 94; The results of the questionnaire showed that the overall content of the approval scheme was "better than the original nursing routine" (59. 18%); The recognition of "common symptoms" (36. 70%) and "syndrome classification" (36. 70%) was the lowest. Conclusion In the future, efforts should be made to widely collect the clinical user experience and suggestions of TCM nursing scheme, and further improve the scheme content in combination with the evidence-based concept to make it closer to the clinical practice. (目的 自制中医护理方案的内容质量和临床适用性问卷。并通过问卷调查临床护士对中风急性期与恢复期中医护理方案的质量和临床适用性的评价。方法 参考中医临床诊疗指南适用性调查问卷自行设计调查问卷, 应用专家咨询法进行内容效度评价。选取9所医院的49名护士进行问卷调查, 对问卷结果应用SPSS20. 0软件进行处理分析。结果 自设问卷的内容效度S-CVI/Ave得分为0. 94; 问卷结果显示: 认可方案整体内容“优于本单位原有护理常规”(59. 18%)的人数最多; 对方案中“常见症状”(36. 70%)与 “证候分类”(36. 70%)的认可度最低。结论 未来需要广泛收集中医护理方案临床使用者体验及建议, 并结合循证理念进一步完善方案内容, 使其更贴近临床实际。)